Rancang Bangun Antena Rotasi Dengan Kalibrasi Berbasis Program Kalman Filter - Rahman, Imam Arief; Rangkuti, Syahban; Agil Abdul Ghani Alghifari K (APIC, 2023)
The Internet of Things (IoT) has changed how we interact with our environment. Low-Power Wide-Area Networks (LPWAN) such as LoRa play an important role in the IoT ecosystem due to their low power consumption, long-distance communication, and cost-effectiveness. However, detecting the azimuth and elevation angles of the transmitter is a challenge in LoRa communication. This paper proposes a rotary antenna system with an Inertial Measurement Unit (IMU) to precisely track azimuth and elevation angles at LoRa. The research carried out is to test the tool by comparing the algorithm without the Kalman Filter and the one with the Kalman Filter, where the test's success with the lowest error is up to 0.75% and 0%, respectively.